(untitled) (Research, Society and Development, 2020)
Standardization of work is an important tool in identifying problems in administrative environments, creating a flow of activities, reducing procedural variations, determining best practices to promote quality of service. The purpose of this paper is to show the benefits of standardization using the POP (Standard Operating Procedure) in the digital certification process. The methodology used was the bibliographical and field research. The field research consisted of a case study at a Brokerage Firm specializing in the issuance of digital certificates located in the region of Campinas/SP. The actual changes were registered with the standardization of activities related to the purchase and validation of the digital certificate e-CNPJ A1 using POP with the purpose of promoting agility in the processes. Overall, the results were positive, meeting the expectations previously established for the standardization process. There was a reduction in the mean time of the processes for the validation step. The average reduction of 10 minutes in customer service was verified, making the digital certification process in the studied company established within the limit classified as the ideal.